2019
DOI: 10.1186/s12960-019-0426-9
|View full text |Cite
|
Sign up to set email alerts
|

Reforming medical education admission and training in low- and middle-income countries: who gets admitted and why it matters

Abstract: Recent studies reveal public-sector healthcare providers in low- and middle-income countries (LMICs) are frequently absent from work, solicit informal payments for service delivery, and engage in disrespectful or abusive treatment of patients. While extrinsic factors may foster and facilitate these negative practices, it is not often feasible to alter the external environment in low-resource settings. In contrast, healthcare professionals with strong intrinsic motivation and a desire to serve the needs of thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 13 publications
1
13
0
1
Order By: Relevance
“…In response to the rapid development of medical science and the need for hospitals to maintain work efficiency to save human resources, the main type of continuing medical education is currently in-service training, which includes online learning. 29 30 In-service training and online training may save time and money because they are less likely to negatively affect physicians’ workload than onsite DT or OS. Therefore, it is important to determine the extent to which off-the-job training can improve physicians’ work performance.…”
Section: Discussionmentioning
confidence: 99%
“…In response to the rapid development of medical science and the need for hospitals to maintain work efficiency to save human resources, the main type of continuing medical education is currently in-service training, which includes online learning. 29 30 In-service training and online training may save time and money because they are less likely to negatively affect physicians’ workload than onsite DT or OS. Therefore, it is important to determine the extent to which off-the-job training can improve physicians’ work performance.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in other countries, including lower and middleincome countries, strongly suggest that students' social background and geographical origins are important predictors of career choice and that students from rural areas are more likely than those from urban areas to work in rural environments after initial training. 10 The Training for Health Equity Graduate Outcome Study reported that "rural and low income background and regional location of medical school were the most important predictors of intent to practice in a rural location". 11 Whether or not this applies to the PNG situation is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers at the health-care provider level include inadequate quantity and quality of health-care workers to provide surveillance, research, prevention, acute care and rehabilitation services. In LRSs, health-care systems depend heavily on individual performance of the few available health workers, who are often overstretched by high disease burdens and workforce shortages 7 . Poor motivation can lead to negative provider behaviour, such as absenteeism, poor communication and discourteous treatment of patients, which in turn leads to distrust and reduced use of the service 7 .…”
mentioning
confidence: 99%
“…In LRSs, health-care systems depend heavily on individual performance of the few available health workers, who are often overstretched by high disease burdens and workforce shortages 7 . Poor motivation can lead to negative provider behaviour, such as absenteeism, poor communication and discourteous treatment of patients, which in turn leads to distrust and reduced use of the service 7 . The negative effects of these actions are frequently overlooked by policy makers and administrators owing to low levels of accountability.…”
mentioning
confidence: 99%
See 1 more Smart Citation